The joint dynamics of money and credit multipliers since the gold standard era - Luca Benati (University of Bern, Department of Economics, 2021)
Since the XIX century, technological progress has allowed commercial banks to create ever greater amounts of broad money and credit starting from a unit of monetary base. Crucially, however, at the very low frequencies the relative amounts of the two aggregates created out of a unit of base money have remained unchanged over time in each of the 42 countries I analyze. This finding questions the widespread notion that, since WWII, credit has become disconnected from broad money, and suggests that, except for their greater productivity at creating broad money and credit out of base money, today's commercial banks are not fundamentally different from their XIX century's counterparts. The implication is that only the ascent of shadow banks has introduced a disconnect between broad money and credit.
Keywords: 330; Money; credit; Lucas critique; financial crises